GABAB receptors enhance excitatory responses in isolated rat retinal ganglion cells. (14th June 2016) - Garaycochea, Jay; Slaughter, Malcolm M.
Abstract : Key points: GABA is an inhibitory transmitter but can sometimes produce paradoxical excitatory effects through synaptic networks. We found a novel GABA‐mediated excitation within a single retinal cell. It involves a chain of events from receptor stimulation to the sequential modulation of two associated channels, resulting in enhanced neuroexcitability. GABAB receptor activation selectively suppresses N‐type calcium channels. The BK‐type potassium channels are exclusively linked to the N‐type calcium channel. Thus, stimulation of GABAB receptors suppresses an outward current, increasing the excitatory range of single neurons. Abstract: GABAB receptors (GABAB Rs) suppress voltage‐gated calcium channels and activate G‐protein coupled potassium channels (GIRK and TREK channels), both mechanisms serving to inhibit neurons. In isolated rat retinal spiking neurons, GABAB Rs produce both actions but the net effect is to enhance excitatory signals. This is because GABAB Rs selectively suppress N‐type calcium channels, which in turn are specifically linked to BK channels. Consequently, when GABAB Rs are stimulated there is a reduction in outward current, allowing neurons to extend their level of depolarization. Whereas many retinal neurons use L‐type channels to stimulate vesicle fusion, the suppression of N‐type channels augments dynamic range without affecting transmitter release. Key points: GABA is an inhibitory transmitter but can sometimes produce paradoxical excitatory effects through synaptic networks. We found a novel GABA‐mediated excitation within a single retinal cell. It involves a chain of events from receptor stimulation to the sequential modulation of two associated channels, resulting in enhanced neuroexcitability. GABAB receptor activation selectively suppresses N‐type calcium channels. The BK‐type potassium channels are exclusively linked to the N‐type calcium channel. Thus, stimulation of GABAB receptors suppresses an outward current, increasing the excitatory range of single neurons.